Community Empowerment in Preventing Drug Abuse - Rasmanah, Manah; Jannati, Zhila; Komaruddin (Wardah, 2024)
This research-based service research departs from the problem of drug abuse in Mulyorejo village, taking into account the strategic geographical location for drug trafficking, the surrounding villages' high drug case rates, and the public's lack of understanding of the dangers of drugs. This drug problem has existed for a long time, but neither the government nor the community has made any effort to address it. The community assistance approach used was Asset-based Community Driven Development (ABCD), a method of community empowerment that draws on the community's strengths, potential, and assets to overcome problems and promote community development. The ABCD approach comprises five stages: inculturation, discovery, design, definition, and reflection. The Women and Children Forum's empowerment process has resulted in several outcomes, including the realization by the assisted community that they have numerous assets/potentials that can be used to develop and solve problems, particularly drug abuse. The assisted community understood the dangers of drugs and was aware of the importance of prevention. The assisted community could identify needs and develop activity plans to address drug abuse issues. The assisted community could also engage in activities such as drug danger socialization, drug alert family strengthening, and drug abuse prevention advocacy with village governments and religious institutions.